2014
DOI: 10.1021/ic5026153
|View full text |Cite
|
Sign up to set email alerts
|

Carbon–Hydrogen Bond Activation, C–N Bond Coupling, and Cycloaddition Reactivity of a Three-Coordinate Nickel Complex Featuring a Terminal Imido Ligand

Abstract: The three-coordinate imidos (dtbpe)Ni=NR (dtbpe = tBu2PCH2CH2PtBu2, R = 2,6-iPr2C6H3, 2,4,6-Me3C6H2 (Mes), and 1-adamantyl (Ad)), which contain a legitimate Ni–N double bond as well as basic imido nitrogen based on theoretical analysis, readily deprotonate HC≡CPh to form the amide acetylide species (dtbpe)Ni{NH(Ar)}(C≡CPh). In the case of R = 2,6-iPr2C6H3, reductive carbonylation results in formation of the (dtbpe)Ni(CO)2 along with the N–C coupled product keteneimine PhCH=C=N(2,6- iPr2C6H3). Given the ability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
48
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 60 publications
1
48
0
Order By: Relevance
“…In nickel chemistry, it is generally observed that small 2 J P, P (i.e.,2 -30 Hz) correspond to nickel(II) complexes, whereas larger 2 J P, P (i.e.,4 5-80 Hz) correspond to nickel(0) complexes. [10,11,22,[77][78][79][80][81][82][83][84] However, exceptionst ot his trend have been reported by ourselves [10] and others. [84,85] Moreover,this approach is limited to asymmetric speciesb ecause 2 J P, P cannotb eo bserved in complexes such as 4 and 7 due to symmetry.…”
Section: Nmr Spectroscopymentioning
confidence: 93%
“…In nickel chemistry, it is generally observed that small 2 J P, P (i.e.,2 -30 Hz) correspond to nickel(II) complexes, whereas larger 2 J P, P (i.e.,4 5-80 Hz) correspond to nickel(0) complexes. [10,11,22,[77][78][79][80][81][82][83][84] However, exceptionst ot his trend have been reported by ourselves [10] and others. [84,85] Moreover,this approach is limited to asymmetric speciesb ecause 2 J P, P cannotb eo bserved in complexes such as 4 and 7 due to symmetry.…”
Section: Nmr Spectroscopymentioning
confidence: 93%
“…A [4+2] cycloaddition product ( 7 , see Supporting Information) is also observed for benzophenone. In contrast, TM–imido complexes undergo [2+2] cycloadditions with benzaldehyde or benzophenone …”
Section: Methodsmentioning
confidence: 99%
“…5,6 A number of late transition metal carbene (CR 2 2-), nitrene (NR 2-), nitride (N 3-), and phosphinidene (PR 2-) complexes have also been reported in recent years. [7][8][9][10][11][12][13][14][15][16][17][18] While a few of these complexes have been isolated, they tend to be extremely reactive, and often can only be observed spectroscopically. [19][20][21][22] Nonetheless, it is clear that synthetic chemists are now beginning to identify the combination of ligand requirements and synthetic procedures that can successfully generate late-metal ligand multiple bonds.…”
Section: Introductionmentioning
confidence: 99%